2022
DOI: 10.5093/clysa2022a13
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Healthcare Experience and Perinatal Depression during COVID-19 Pandemic

Abstract: Background: The prevalence of peripartum depression (PPD) has increased substantially since the start of the COVID-19 pandemic. To reduce the probability of contagion, hospitals had to adapt their care protocols, including the care of women in the perinatal period. Method: A cross-sectional study was used in a total sample of 3,356 women, 1,402 in the prenatal period and 1,954 in the postnatal period. They completed the Edinburgh Postnatal Depression Scale to assess depressive symptoms and the Spanish version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This may suggest that increased resilience among infertile women could decrease the effect from stress, thereby reducing the impact on anxiety symptoms. A previous study reported additional reduction of maternal stress through support from health care providers (Kovacheva et al, 2022). Resilience accounted for more than double of the variance in anxiety symptoms compared to optimism which shows that resilience seems to be more important in explaining anxiety symptoms than optimism.…”
Section: Discussionmentioning
confidence: 73%
“…This may suggest that increased resilience among infertile women could decrease the effect from stress, thereby reducing the impact on anxiety symptoms. A previous study reported additional reduction of maternal stress through support from health care providers (Kovacheva et al, 2022). Resilience accounted for more than double of the variance in anxiety symptoms compared to optimism which shows that resilience seems to be more important in explaining anxiety symptoms than optimism.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, it should be noticed that all the participants were pregnant women over 18 years of age, who spoke Spanish, and were users of the regional health system of Andalusia and could not have had a history of psychopathological problems and may have developed them during the pandemic, since mental health problems that affect pregnancy, childbirth, and the postpartum period could arise spontaneously (Stranges et al, 2014). The results showed the importance of giving healthcare professionals strategies or protocols based on prevention (Kovacheva et al, 2022) to care for those women affected. An appropriate technique claimed by other researchers appears to be the cognitive behavioural therapy, even if this technique is used online (Puertas-Gonzalez, Mariño-Narvaez, Puertas-Gonzalez et al, 2022).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This risk has been increased during the pandemic (Kovacheva et al, 2022;Motrico et al, 2020;Preis et al, 2020) as a result of the control measures imposed during its critical phases to control its spread (isolation, solitude, social distancing) or the fear of infection. The psychological effects of these measures were already present in the early pandemic phases (Pfefferbaum & North, 2020;Wang et al, 2020).…”
Section: Pandemic Played a Rolementioning
confidence: 99%
“…Depression is the most common psychological disorder during the perinatal period ( 1 ), making it a major public health problem, with a global prevalence around 11.9% ( 2 ). This prevalence has increased in recent years due to COVID-19, reaching a prevalence ranging from 22 to 31% ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%